(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In this article, the education of Eastern thinkers opinions about what a perfect person should be, the place of education in human life, and information on raising children in the family. This article describes the importance of education issues in personal development and its value today.